2019
DOI: 10.1101/745026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nuclear receptor NR4A1 is regulated by SUMO modification to induce autophagic cell death

Abstract: 242 25 Abstract 26 NR4A is a nuclear receptor protein family whose members act as sensors of cellular 27 environment and regulate multiple processes such as metabolism, proliferation, migration, 28 apoptosis, and autophagy. Since the ligand binding domains of these receptors have no 29 cavity for ligand interaction, their function is most likely regulated by protein abundance 30 and post-translational modifications. In particular, NR4A1 is regulated by protein 31 abundance, phosphorylation, and subcellular dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…39 Such paradoxical role of SUMOylation remains unexplained, but recent studies in which both sites well conserved in Nur77 were mutated together suggested a combined effect of SUMOylation in regulating Nur77 activity and degradation. 38,72 Consistent with additional SUMOylation that might also occur in Nor1, our results show that the K137R Nor1 mutant still exhibits a SUMOylation signal sensitive to SENP1, strongly supporting the presence of other potential SUMO conjugation site(s) in Nor1. Of the two canonical SUMO motifs found in Nor1, Lys-89 is a likely candidate based on its strong predictive value and homology with Nurr1, but Lys-606 also needs to be considered.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…39 Such paradoxical role of SUMOylation remains unexplained, but recent studies in which both sites well conserved in Nur77 were mutated together suggested a combined effect of SUMOylation in regulating Nur77 activity and degradation. 38,72 Consistent with additional SUMOylation that might also occur in Nor1, our results show that the K137R Nor1 mutant still exhibits a SUMOylation signal sensitive to SENP1, strongly supporting the presence of other potential SUMO conjugation site(s) in Nor1. Of the two canonical SUMO motifs found in Nor1, Lys-89 is a likely candidate based on its strong predictive value and homology with Nurr1, but Lys-606 also needs to be considered.…”
Section: Discussionsupporting
confidence: 79%
“…SUMOylation at Lys‐577 of Nurr1 has been linked to transcriptional activation 71 and transrepression, 12 whereas SUMOylation at Lys‐91, also contained in a canonical ψKxE motif, was associated with transcriptional inhibition 39 . Such paradoxical role of SUMOylation remains unexplained, but recent studies in which both sites well conserved in Nur77 were mutated together suggested a combined effect of SUMOylation in regulating Nur77 activity and degradation 38,72 . Consistent with additional SUMOylation that might also occur in Nor1, our results show that the K137R Nor1 mutant still exhibits a SUMOylation signal sensitive to SENP1, strongly supporting the presence of other potential SUMO conjugation site(s) in Nor1.…”
Section: Discussionsupporting
confidence: 79%
“…In line with this hypothesis, it has been shown that NUR77 degradation is controlled by SUMOylation and later ubiquitination, and that for the SUMOylation of NUR77 the protein must be previously phosphorylated. 39,40 In view of these results, it is tempting to speculate that deletion of Ptn may be associated in the liver with altered transcriptional activity modulated by glycerol kinase, impairing the pregnancy-related adaptations in both glucose and lipid metabolism, including glucose intolerance and a decreased capacity to store lipids (Figure 9). The mouse is an important mammalian model to approach the study of human metabolism in pregnancy, particularly at a molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as IL-2 supply, co-stimulatory signals on distinct APC populations, or developmental context may be instructive (62). Another possible determinant is intensity/duration/biased signal transduction downstream of the TCR itself, which may in turn guide localization of NR4As to the cytosol or nucleus via posttranslational modifications (69).…”
Section: Discussionmentioning
confidence: 99%